Gifted entrepreneurs 'giftpreneurs' / Dr Rossidi Usop - Usop, Rossidi (UiTM Cawangan Negeri Sembilan, 2022)
In this article, the new concept of gifted entrepreneurs, which is an important key to the economic development of a country, will be presented. The gifted entrepreneur refers to an individual who successfully carries out new business ventures. He or she always starts with an idea and finishes with real products, services, or processes. As well, a gifted entrepreneur is associated with a high degree of practical intelligence, creative, and innovative abilities, as well as managerial and business talent (Larisa V. Shavinina, 2013). In the era of Artificial Intelligence (AI) and Robotics, entrepreneurship is one of the catalysts related to the economy, enhancing innovation, creativity, and competitiveness for a country. Hence, the gifted person is primarily responsible for innovations worldwide and innovations are at the heart of today’s economy (Larissa 2013; Drucker, 1993). In other words, this is why innovation is closely related to giftedness, and why giftedness is related to the economy.